Nutrition and Pregnancy after Bariatric Surgery. (30th January 2013) - Kaska, Lukasz; Kobiela, Jarek; Abacjew-Chmylko, Anna; Chmylko, Lukasz; Wojanowska-Pindel, Magdalena; Kobiela, Paulina; Walerzak, Anna; Makarewicz, Wojciech; Proczko-Markuszewska, Monika; Stefaniak, Tomasz
Abstract : Obesity is an escalating problem in all age groups and it is observed to be more common in females than males. About 25% of women meet the criteria of obesity and one-third of them are in the reproductive age. Because morbid obesity requiring surgical treatment is observed with increasing frequency, surgeons and gynecologists are undergoing new challenges. It is not only a matter of women's health and their quality of life but also proper development of the fetus, which should be a concern during bariatric treatment. Therefore complex perinatal care has to be provided for morbid obesity patients. The paper reviews pregnancy and fertility issues in bariatric surgery patients.